Workplace violence and its associated factors among nurses working in public hospitals of eastern Ethiopia: a cross-sectional study - Henok Legesse; Nega Assefa; Dejene Tesfaye; Simon Birhanu; Seid Tesi; Fenta Wondimneh; Agumasie Semahegn (BMC Nursing, 2022)
Abstract Background Workplace violence is one of the global health concerns. Although nurses are the backbone of the health care provision, they are highly subjected to workplace violence in healthcare. Nevertheless, there is a paucity of evidence on the extent of workplace violence against nurses in Ethiopia in general and Eastern Ethiopia in particular. Hence, this study aimed to assess the extent of workplace violence against nurses and its associated factors among nurse professionals working at public hospitals in eastern Ethiopia. Methods Hospital-based cross-sectional study was conducted among 603 nurses working in public hospitals in eastern Ethiopia. Nurses were recruited using a simple random sampling method at their workplace (health facilities). A pretested self-administered questionnaire was used to collect data. Descriptive, binary and multivariable logistic regression analyses were performed. The adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to declare significant association. Results Among the 620 estimated sample, 603(97.3%) of the nurses gave consent and completed the self-administered questionnaire. The prevalence of workplace violence against nurse professionals in the last 12 months was 64.0% (95%CI: 60.2–67.7%). Nurses who were working in surgical (AOR: 2.30, 95%CI: 1.01–5.26), psychiatric (AOR: 3.06, 95%CI: 1.11–8.46), emergency (AOR: 3.62, 95%CI: 1.46–8.98), and medical wards (AOR: 5.20, 95%CI: 2.40–11.27); being worried of workplace violence (AOR: 1.71, 95%CI: 1.09–2.69); witnessed of physical workplace violence (AOR: 5.31, 95%CI: 3.28–8.59); claimed “absence/not-aware” of reporting procedure on workplace violence (AOR: 2.24, 95%CI: 1.45–3.46); and claimed “absence/not-aware” of institutional policies against workplace violence (AOR: 2.68, 95%CI: 1.73–4.13) were factors associated with nurses’ experience of workplace violence in eastern Ethiopia. Conclusions Workplace violence against nurses was found to be unacceptably high in the study area (eastern Ethiopia). We suggest that stakeholders could work on early risk identification and management of violent incidents, establish violence reporting and sanction mechanisms using contextual strategies to prevent workplace violence against nurse professionals.